1998
DOI: 10.1046/j.1365-2141.1998.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity in acute myelogenous leukaemia: clinical and biological implications

Abstract: Summary. We examined telomerase activity in myeloid leukaemic cell lines, normal haemopoietic cells, and leukaemic blasts from acute myelogenous leukaemia (AML) patients. Normal bone marrow mononuclear (BMNC) cells expressed low telomerase activity. Higher telomerase activity was detected in 10 myeloid leukaemic cell lines compared to normal BMNC cells. Treatment with 1,25(OH) 2 D 3 , and vitamin D 3 analogues, EB1089 and KH1060, reduced telomerase activity in vitamin D 3 -sensitive HL-60 cells, whereas vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…This is similar to findings obtained by the TRAP method (73-100%) [13,[17][18][19]. In our study, no significant difference of hTERT mRNA levels was noted between diagnosis and relapse (P > 0.05); in contrast, Xu et al observed that telomerase activity was significantly higher during relapse than at diagnosis [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to findings obtained by the TRAP method (73-100%) [13,[17][18][19]. In our study, no significant difference of hTERT mRNA levels was noted between diagnosis and relapse (P > 0.05); in contrast, Xu et al observed that telomerase activity was significantly higher during relapse than at diagnosis [13].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, hTERT mRNA expression was not associated with CD34 expression, white blood cell count, blast count, or chromosomal abnormalities (P > 0.05). Other studies have associated poor prognostic parameters with up-regulation of telomerase activity [13,19]. The level of telomerase activity of normal hematopoietic cells is determined by the stage of differentiation and proliferation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme telomerase, by maintaining telomeres at a certain minimum length, can extend the proliferative lifespan of cells [12]. High levels of telomerase activity (TA) are present in fetal hemopoietic stem cells [13], play a role in the immortalization of cells [14], and are characteristic of most malignancies [15]. Human telomerase comprises two major components: human telomerase RNA (hTR), which consists of 451 bases of integral RNA providing the template for the synthesis of the human telomeric repeat (TTAGGG)n [16], and human telomerase reverse transcriptase (hTERT), which is a 127-kDa protein providing catalytic function to replicate the ends of linear DNA [17].…”
Section: Introductionmentioning
confidence: 99%
“…N ormal human somatic cells progressively lose their telomeric sequence with repli cative senscence till cell "crisis" or apoptosis occurred [4,18,19] . I n contrast, almost all tumor cells and tissues express telomerase and maintain telomere length through an indefinite number of cell divisions [4][5][6][7][8][9][10][19][20][21][22][23][24] . Antisense hTR, hammerhead ribozyme TeloRZ and antisense oligonucleode agains t hTR could suppress tumor cell growth by inhibiting telomerase activity or shor tening TRF length [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%